2022
DOI: 10.1101/2022.03.03.482906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dorsolateral striatum, not motor cortex, is a bottleneck for responding to task-relevant stimuli in a learned whisker detection task in mice

Abstract: A learned sensory-motor behavior engages multiple brain regions, including the neocortex and the basal ganglia. How these brain regions coordinate to affect sensory selection (for target stimuli) and inhibition (for distractor stimuli) remains unknown. Here, we performed laminar electrophysiological recordings and muscimol inactivation in frontal cortex and dorsolateral striatum to determine the representations within and functions of each region during selective detection performance. From the recording exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 123 publications
(212 reference statements)
0
4
0
Order By: Relevance
“…Additionally, we have considered why ‘spillover’ of distractor responses into target-aligned S1 would impair distractor response suppression. In a concurrent study (Zareian et al, 2022), we demonstrate that activation of target-aligned dorsolateral striatum (DLS) is critical for response triggering, for both target and distractor stimuli. Whisker-evoked responses propagate widely and across hemispheres in naïve rodents (Aronoff et al, 2010; Aruljothi et al, 2020; Ferezou et al, 2007; Pala & Stanley, 2022).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Additionally, we have considered why ‘spillover’ of distractor responses into target-aligned S1 would impair distractor response suppression. In a concurrent study (Zareian et al, 2022), we demonstrate that activation of target-aligned dorsolateral striatum (DLS) is critical for response triggering, for both target and distractor stimuli. Whisker-evoked responses propagate widely and across hemispheres in naïve rodents (Aronoff et al, 2010; Aruljothi et al, 2020; Ferezou et al, 2007; Pala & Stanley, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…For combined behavioral-physiological studies, an important consideration is whether the task-related neuronal signals could be fully or partially accounted for by movement (Zagha et al, 2022). A specific concern for our study is whether the apparent asymmetric stimulus selectivity, and its modulations by wMC, is instead reflecting movement on 'Go' trials in our Go/No-Go task design (which are more prevalent on target than distractor trials in expert mice, Aruljothi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental protocols have been approved by the IACUC of University of California, Riverside. The dataset used here include behavioral studies that have been previously reported (Aruljothi et al, 2020; Marrero et al, 2022; Zareian et al, 2022; Zareian et al, 2021; Zhang & Zagha, 2022). A wide variety of wild type and transgenic mice were considered for behavioral learning data.…”
Section: Methodsmentioning
confidence: 99%